Methods and methodologies in second language writing research. (July 2016) - Hyland, Ken
Abstract: A considerable variety of methods have been used to understand the complex, multifaceted nature of L2 writing. Often driven by pedagogical imperatives and informed by particular views of writing, texts and writers, these methods themselves raise questions regarding what we believe writing is and about our interpretive practices. With increasing numbers of teachers and scholars turning to investigate writing in their classrooms or courses of further study, it may be helpful to be aware of what options are available for studying writing and how these relate to key methodological designs. More than this, however, it is important to be aware of what our choices imply about our understanding of what writing is and how it can be known. In this paper I set out the main approaches to studying writing for novice researchers, providing examples of key studies, and go on to situate these methods within the main theories about writing arguing that methods are not neutral options but allow us to see certain things but not others. They do not just tell us different things about writing but reveal what we believe writing to be.